Torrenticolid water mites (Acari: Hydrachnidia: Torrenticolidae) from Malaysian Borneo - Pešić, Vladimir; Smit, Harry (Zootaxa, 2014)
New records of water mites of the family Torrenticolidae (Acari: Hydrachnidia) from streams in two mountain ranges in northern Borneo are presented. Aims of this study were to reconstruct phylogenetic relationships of the newly collected torrenticolids using molecular methods, and describe all new species. A fragment of the mtCOI gene was successfully PCR-amplified from 18 torrenticolid specimens and 14 new species are described: Torrenticola (Torrenticola) borneoensis n. sp., T. (T.) kinabaluensis n. sp., T. (T.) sabahensis n. sp., T. (T.) neoindica n. sp., T. (T.) schilthuizeni n. sp., Neoatractides (Allotorrenticola) sundaensis n. sp., N. (Heteratractides) uniscutatus n. sp., Pseudotorrenticola borneoensis n. sp., Monatractides (Monatractides) epiales n. sp., M. (M.) morpheus n. sp., M. (M.) phantasos n. sp., M. (M.) phobetor n. sp., M. (M.) hercules n. sp. and M. (M.) minuta n. sp. Additionally, the first records for Borneo are given for Torrenticola (Megapalpis) cf. pugionirostris (K. Viets, 1939), Monatractides (Monatractides) longiventris (K. Viets, 1939), M. (M.) cf. macroporus (K. Viets, 1935) and M. (M.) oxystomus (K. Viets, 1935). Monatractides tobaensis (K. Viets, 1935) is transferred to the subgenus Vietsclio Pešić & Smit, 2014. A key to the species of Monatractides is presented.